Development of an eeg amplifier for real-time acquisition - Izadora, Mustaffa; Low , Yin Fen; Norhashimah , Mohd Saad (2006)
Electroencephalography (EEG) are primarily use for diagnosis, detect and localize cerebral brain lesions, aid in the studying of epilepsy, diagnosing mental disorders, assist in diagnosing sleep patterns and allowing observation and analysis of brain responses to sensory stimuli. To date, advance researchers have developed system that use EEG signals to decipher thoughts so that a person can communicate by means of ain activity brain activity alone. The purpose of this project is to develop an EEG amplifier that forms part of an EEG signal acquisition system with the intention to form a basis for EEG research. The hardware includes amplifications and filtering circuit and a personal computer (PC) while the software allows to store the recorded EEG data in all-time.